2021
DOI: 10.1021/acsami.1c04680
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic Cascade Reactions Mediated by Highly Efficient Biomimetic Quasi Metal–Organic Frameworks

Abstract: The integration of chemo- and enzymatic catalysis for effective multistep cascades has presented critical challenges for decades. In this work, the biomimetic quasi NH2-MIL-101 (qNM) with highly efficient peroxidase-like activity was synthesized via a palmitic acid-induced strategy followed by pyrolysis. The effects of the amount of palmitic acid and calcination temperature on the synthesis of qNM were optimized. It was found that qNM was an excellent catalyst for oxidations of various peroxidase substrates, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 71 publications
1
28
0
1
Order By: Relevance
“…Iron-based MOFs or derived materials exhibit excellent sensing performances because of their potential redox ability and stability when used as electrode materials. , Construction of electrode materials with a microstructure and uniform morphology is an effectual strategy to strengthen their electrochemical characteristics . The nickel/nickel-based electrodes find great applications in electrochemical devices, supercapacitors, and fuel cells as electrode materials.…”
Section: Resultsmentioning
confidence: 99%
“…Iron-based MOFs or derived materials exhibit excellent sensing performances because of their potential redox ability and stability when used as electrode materials. , Construction of electrode materials with a microstructure and uniform morphology is an effectual strategy to strengthen their electrochemical characteristics . The nickel/nickel-based electrodes find great applications in electrochemical devices, supercapacitors, and fuel cells as electrode materials.…”
Section: Resultsmentioning
confidence: 99%
“…Nowadays, various nanozymes have been served as catalytic labels for multi-category signal amplification in newly developed immunoassays. Numerous studies revealed that metal NPs (Au, Ag, Pt, Pd) [85,86], metal oxide NPs (Fe 3 O 4 , CeO 2 , MnO 2 , CuO) [87][88][89][90][91][92], carbon-based (graphene oxide, carbon nitride, carbon dots) [93][94][95][96], and MOFs-based nanomaterials [97][98][99] with peroxidase-, catalase-, oxidase-, superoxide dismutase-mimicking properties.…”
Section: Nanozyme For Signal Amplificationmentioning
confidence: 99%
“…MOFs have been applied as the attractive solid supports for enzymes not only for their being inert hosts but also to enhance the stability or activity of the enzymes. A series of reported for immobilizing enzymes in MOF have been published. MOFs could increase the resiliency of enzymes. For example, immobilization enzyme in the MOF support could prevent its unfolding and losing reaction activity when it is exposed to the bad reaction conditions, for example, high temperature. , …”
Section: Introductionmentioning
confidence: 99%